Village Projects Observed in Eritrea: Post-Conflict Pathways towards Democratic Rural Development - Gregory Cameron (Modern Africa)
Eritrea’s rural development trajectory has fallen short of fully meeting the basic needs of its peasants and pastoralists, let alone national food security objectives. This article builds on earlier research on rural development projects in a select number of villages. These projects were primarily characterised by a state-centric technocratic logic that did, to some degree, embed “hard” infrastructure in the villages, but which paid less attention to building village-level capacity or organisational autonomy. Looking beyond these impasses, the present article suggests an inward-oriented national development model centred on the home market, rural co-operatives, and food sovereignty. As yet ‒ at the time of writing ‒ another major war afflicts Eritrea and Ethiopia, the presence of the political will for such a transition is by no means guaranteed.